Multicomponent metal-organic frameworks : tailoring platforms for transition metal- and bioelectrocatalysis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University, Manawatū, New Zealand - Auer, Bernhard Stephan (Massey University, 2025)
MUF-77 (MUF = Massey University Framework) is a quaternary, multicomponent metal-organic framework (MOF), constructed from three topologically distinct carboxylate linkers and Zn4O secondary building units. Multicomponent MOFs such as MUF-77, constructed from a set of ligands with different geometries, provide a valuable platform for obtaining ordered and programmable pore environments. In this context, they show great potential as recyclable and stable, heterogeneous catalysts. In this work, we looked at the typical MUF 77 synthesis conditions and investigated the formation of additional crystalline phases. Several new MOFs were discovered, including new multicomponent MOFs. We then investigated MUF-77 for the incorporation of transition metal catalysts. The work included ligand and MOF syntheses and synthetic modifications of the frameworks upon MOF formation. We also embedded a Au(III) catalyst within the MUF 77 framework and evaluated its catalytic properties upon installation into the framework. Finally, we shifted our focus to systems comprising MOF and enzyme components for their electrochemical application in layer-by-layer-grafted electrodes. The work extended our library of potential heterogeneous catalysts, showcasing the great potential of multicomponent systems.
Keywords: MOF, metal-organic framework, MUF-77, catalysis, catalyst, transition metal catalyst, gold, bioelectrocatalysis, electrodes, electrochemical applications, enzyme catalysis, heterogeneous catalysis, porous materials; Metal-organic frameworks; Heterogeneous catalysis; Catalysts; 340207 Metal organic frameworks; 340601 Catalysis and mechanisms of reactions